The Acceptance of Organizational Restructuring of Employees from The Provincial Electricity Authority, Phetchaburi Province - Samarnmit, Puttichai; Sunalai, Suravee (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research study aimed to 1) compare the acceptance of organizational restructuring of employees from the PEA (Provincial Electricity Authority) in Phetchaburi province, classified by personal factors; and 2) investigate the impacts arising from the perception of the employees from the PEA in Phetchaburi province towards the acceptance of organizational restructuring. Quantitative analysis using an online questionnaire survey was used to collect data 235 employees out of 279 employees from the PEA in Phetchaburi province (84%). The hypotheses were analyzed using Independent Sample t-test, One-way ANOVA, and Multiple Regression Analysis. The findings showed that: 1) the acceptance of organizational restructuring of the employees from the PEA in Phetchaburi province, classified by education background, division, work position, and work experience was significantly different, whereas the acceptance of organizational restructuring classified by age was not significantly different and 2) the perception of organizational restructuring, which explain the variation of the perception of organizational restructuring with the percentage of 75.0, when considering independent variables included the acknowledgement of organizational restructuring (X1), duties and responsibility (X2), and organizational restructuring process (X4). The equation of regression analysis was Y = 0.348 + 0.434(X1) + 0.256(X2) + 0.303(X4). Article history: Received 27 October 2022 Revised 14 May 2023 Accepted 16 May 2023 SIMILARITY INDEX = 2.46 %